EFEKTIVITAS TERAPI KONSELING KELUARGA DENGAN PENDEKATAN COGNITIVE BEHAVIORAL THERAPY PADA PASANGAN/KELUARGA YANG MENGALAMI KONFLIK/KEKACAUAN DALAM HUBUNGAN PERNIKAHAN - Wulan, Winda Ratna; Rohim, Abdal; Nur, Ayip Syaripudin (Journal Healthcare Education, 2024)
Cognitive Behavioral Therapy (CBT) has been widely used as an effective and efficient therapeutic strategy for managing various mental disorders in both developed and developing countries. However, each modification of CBT counseling services provided to families, particularly those with marital conflicts, will inevitably have varying levels of effectiveness. Therefore, a scientific study is needed to provide an overview of how effective CBT counseling is for families, even with various modifications. The purpose of this study is to systematically review and analyze the effects of CBT on families with marital conflicts, considering modifications in the content and duration of the sessions provided. The research method involves a literature review by collecting sources from databases such as TOJDAC, SCI, International Journal of Medical Research & Health Sciences, IJHCS, and the Iranian Journal of Educational Sociology, while establishing inclusion and exclusion criteria. The study results, derived from the analysis of four pieces of literature on cognitive behavioral therapy, indicate that families or couples who receive CBT counseling are generally better at managing and resolving family conflicts, particularly marital conflicts, compared to those who do not receive therapy.